Экологические особенности хищного клеща Amblyseius longispinosus - Колодочка, Л.А. (Вестник зоологии, 1983)
Under optimal conditions, demographic parameters of Amblyseius longispinosus appeared to be higher than in other species of the genus. Population increase rate at the feeding on spider mite eggs is higher than on deutonymphs. A. longispinosus is found to be promising as a biological agent of spider mite control.